Autosomal dominant hereditary spastic paraplegia with axonal sensory motor polyneuropathy maps to chromosome 21q 22.3. (2nd July 2016) - Peddareddygari, Leema Reddy; Hanna, Philip A.; Igo, Robert P.; Luo, Yuqun A.; Won, Sungho; Hirano, Michio; Grewal, Raji P.
Abstract : Aim: Hereditary spastic paraplegia (HSP) are a genetically and clinically heterogeneous group of disorders. At present, 19 autosomal dominant loci for HSP have been mapped. We ascertained an American family of European descent segregating an autosomal dominant HSP associated with peripheral neuropathy. Methods: A genome wide scan was performed with 410 microsatellite repeat marker (Weber lab screening set 16) and following linkage and haplotype analysis, fine mapping was performed. Established genes or loci for HSP were excluded by direct sequencing or haplotype analysis. Results: All established loci for HSP were excluded. Fine mapping suggested a locus on chromosome 21q22.3 flanked by markers D21S1411 and D21S1446 with a maximum logarithm of odds score of 2.05 and was supported by haplotype analysis. A number of candidate genes in this region were analyzed and no disease-producing mutations were detected. Conclusion: We present the clinical and genetic analysis of an American family with autosomal dominant HSP with axonal sensory motor polyneuropathy mapping to a novel locus on chromosome 21q22.3 designated SPG56.